Traditional Historical Songs of Russian Old-Timers of Yakutia: Versions of the Song about Count Chernyshev - O. I. Charina (Научный диалог)
The article deals with the characteristics of the song versions devoted to the capture of the count Zakhar Chernyshev in the repertoire of the old-timers living in northeastern Yakutia. The data include the texts of the songs recorded on the Indigirka and the Kolyma. The relevance of the study is due to the following: nowadays the local folklore texts are being studied to define the degree of traditionalism of the plot. The implemented methods such as a descriptive method, a comparative method and some methods of lexicosemantic analysis help to reveal the features of the folklore text. It has been established that the version accepted in Russkoye Ustye and the Kolyma version of the song are similar in images, approaches to the theme and the development of the plot. It is noted that the influence of the Yakut language on these songs is hardly noticeable, in comparison with other historical songs that existed on the Indigirka and the Kolyma. It is shown that continuity and the exact execution of the learned text were important in Russkoye Ustye, whereas changes in the text might have been allowed on the Kolyma. The author comes to the conclusion that there is no accident in the transformation of the leitmotif of the song from the first records, where the character is captured by the Prussians and the theme of will is the main one, to the last recorded versions, in which count Chernyshev is ready to serve the “White Tsar” and the theme of will is hidden.